Simulação numérica da estrutura de escoamento, do spray e da mistura ar/combustível em um motor de ignição por centelha de injeção direta - Leonardo Mayer Reis (2018)
The high demand of the transport sector for vehicles that has lower fuel consumption and emissions levels within the legislation, in other words, an increase in the internal combustion engines efficiency is sought. One way of achieving this improvement is related to the flow structures inside the cylinders, since they are capable to control the mixture formation, the turbulent kinetic energy, the combustion and hence the emissions levels. In this context, the device known as a flow box, which has the function of changing the in-cylinder flow, is presented as an alternative. In addition to this technology, the use of direct injection is a reality as a better control of fuel injection in-cylinder. The present work, through numerical analysis studied the behavior of a single-cylinder research engine in a motored condition, using flow box, which in this case is a plate positioned at the entrance of intake port. Three plates were tested and distinguished by the different fluid flow region position. The turbulence analysis is performed with the RNG k- model. The injection of ethanol and gasoline spray in a quiescent chamber, for pressure swirl and multi-hole injectors were described by the Rosin-rammler droplet size distribution and by the KHRT droplet breakup model. Based on the cases studied, it was cleared the flow box influence on the structures coefficients, being able to change the rotation direction and considerably increase the magnitude of tumble during intake and compression strokes. In addition, its use may provide changes in the turbulent kinetic energy, in-cylinder and spark plug region. The numerical models applied for the description of the sprays shown to be suitable, with good agreement with the liquid penetration curves and spray edge profile. By analyzing the excess air factor lambda, the flow box was able to change its spatial distribution, providing more homogeneous mixtures.